The Effect of Changes in Minimum Wage Rates on Provincial Unemployment Rates, 1970-77 - Maki, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This paper estimates the effect of different minimum wage to average wage ratios among provinces on differences in provincial unemployment rates. The effect is found to be statistically significant, but small in magnitude.